2005
DOI: 10.1590/s0100-29452005000300007
|View full text |Cite
|
Sign up to set email alerts
|

Firmeza de pêssegos 'diamante' tratados com 1-MCP

Abstract: RESUMO -No Brasil, o consumo de pêssegos in natura vem aumentando a cada ano. No entanto, durante o transporte, o período de armazenamento e a comercialização, as perdas são bastante significativas, havendo a necessidade de desenvolver tecnologias para manter a qualidade pós-colheita e prolongar a vida útil desses frutos. O composto 1-metilciclopropeno (1-MCP) vem sendo usado com resultados positivos em diversos tipos de frutos, como goiaba, banana, maçã, entre outras. Neste trabalho, foi avaliado o tratamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Lima et al (2006) studied melons and found that PME can decrease, stay constant or increase, depending on storage conditions. An increase in PME activity was seen by Lourenço and Catutani (1984) in melons, Johnston et al (2002) in apples, Oliveira et al (2005) in peaches, Iannetta et al (1999) in raspberries, Chin et al (1990) in star fruit, Brummell et al (2004) in pears, Hobson (1963) in tomatoes, and Hultin and Levine (1965) in bananas. On the other hand, a decrease in PME activity was seen in avocados by Awad and Young (1979), in mangoes by Prasanna et al (2003), and by Resende et al (2004) in tomatoes.…”
Section: Pme Activitymentioning
confidence: 92%
“…Lima et al (2006) studied melons and found that PME can decrease, stay constant or increase, depending on storage conditions. An increase in PME activity was seen by Lourenço and Catutani (1984) in melons, Johnston et al (2002) in apples, Oliveira et al (2005) in peaches, Iannetta et al (1999) in raspberries, Chin et al (1990) in star fruit, Brummell et al (2004) in pears, Hobson (1963) in tomatoes, and Hultin and Levine (1965) in bananas. On the other hand, a decrease in PME activity was seen in avocados by Awad and Young (1979), in mangoes by Prasanna et al (2003), and by Resende et al (2004) in tomatoes.…”
Section: Pme Activitymentioning
confidence: 92%
“…Pectins act as a cementing material and are found mainly in the cell wall, being responsible for fruit firmness (Álvarez-Herrera et al, 2016). Thus, the 1-MCP promoted less pectin solubilization in the treated figs, which probably caused delay of the ethylene effect on the pectinase enzymes present in the cell wall; consequently, fuit firmness was promoted (Blum and Ayub, 2009;Oliveira et al, 2005;Terra et al, 2014). Ribeiro et al (2012) observed that the resistance grape peels increased when they shriveled in their final ripening stage.…”
Section: Discussionmentioning
confidence: 99%
“…These constitute most of the soluble solids of the strawberries and come mainly in the form of glucose and fructose (4.5%) and sucrose (0.9%) (CHITARRA; CHITARRA, 2005). Oliveira et al (2005) reported that sugar levels usually increase with the fruit ripening, through biosynthesis processes or by polysaccharide degradation. The variations within a same species are due to several factors, such as cultivar, soil type, climatic conditions and cultivation practices.…”
Section: Total Reducing and Non-reducing Sugarsmentioning
confidence: 99%
“…Smooth Cayenne L (THÉ et al, 2001) and in 'Diamante' peach (Prunus persia (L) Batsch) (OLIVEIRA et al, 2005).…”
Section: Total Reducing and Non-reducing Sugarsmentioning
confidence: 99%